KONSEP DASAR ULUMUL QUR’AN - Karman; Ade Andriyani; Asep Purnama Sidiq; Cucu Komariah; Dede Wartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Al-Qur'an as a guide and guide to life for Muslims, is not only limited to Arabic writing written in a mushaf, but the Al-Qur'an is the word of Allah which is the answer to problems or questions that have arisen since the time of the Prophet Muhammad SAW until the end. era. Not a few Muslims today only understand the Al-Qur'an as a book that is mandatory in the Faith, without making any effort to study and understand further the contents of the Al-Qur'an. The obligation to study, understand and apply every content of the Koran will be a solution to make it easier to achieve happiness in this world and the hereafter. Therefore, Ulumul Qur'an as a scientific discipline that discusses the scientific branches of the Qur'an must be studied and understood correctly, so that there are no misinterpretations in understanding the contents of the Qur'an.